Научные основы восстановления запасов зайца-русака на Украине и их эксплуатация - Абеленцев, В.И.; Шевченко, Л.С. (Вестник зоологии, 1975)
﻿On the basis of four-years investigations the number of hares in various biotopes (20 individuals per 1000 ha), their habitat and seasonal distribution, effect of agricultural technique and chemisation on changes in the number, factors determining growth of population and a series of other problems are elucidated. With the aim to restore the hare population it is necessary to stop shooting, to carry out biotechnical measures for preservation of young hares in the period of their reproduction and to create food and fine areas in agricultural lands.